2020
DOI: 10.3389/fmolb.2020.585056
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast and Osteoclast Activity Affect Bone Remodeling Upon Regulation by Mechanical Loading-Induced Leukemia Inhibitory Factor Expression in Osteocytes

Abstract: PurposeBone remodeling is affected by mechanical stimulation. Osteocytes are the primary mechanical load-sensing cells in the bone, and can regulate osteoblast and osteoclast activity, thus playing a key role in bone remodeling. Further, bone mass during exercise is also regulated by Leukemia inhibitory factor (LIF). This study aimed to investigate the role of LIF in the mechanical response of the bone, in vivo and in vitro, and to elucidate the mechanism by which osteocytes secrete LIF to regulate osteoblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…LIF secretion by osteocytes can increase the tartrate-resistant acid phosphatase activity of BMM-derived osteoclasts and enhance alkaline phosphatase activity during the osteogenic differentiation of BMSCs. Mechanistically, LIF increases the phosphorylation of STAT3, which is associated with osteoclast and osteoblast formation [ 108 ] (Fig. 5 ).…”
Section: Cell–cell Interactions Via Stat3 Activationmentioning
confidence: 99%
“…LIF secretion by osteocytes can increase the tartrate-resistant acid phosphatase activity of BMM-derived osteoclasts and enhance alkaline phosphatase activity during the osteogenic differentiation of BMSCs. Mechanistically, LIF increases the phosphorylation of STAT3, which is associated with osteoclast and osteoblast formation [ 108 ] (Fig. 5 ).…”
Section: Cell–cell Interactions Via Stat3 Activationmentioning
confidence: 99%
“…A recent study showed that the leukemia inhibitory factor (LIF) enhanced signal transducer and activator of transcription 3 (STAT3) phosphorylation in BMSCs and increased the expression of ALP and osteogenic genes. However, in the in vitro microgravity environment, the secretion of LIF by bone cells was inhibited, which weakened the osteogenic effect ( Du et al, 2020 ). Microgravity also increases the level of oxidative damage markers in the body and weakens the total antioxidant capacity.…”
Section: Mechanical Stimulation With Osteoblastsmentioning
confidence: 99%
“…Leukemia inhibitory factor (LIF) is a member of the interleukin-6 family of cytokines with highly pleiotropic biological activities. LIF expression has been reported for all three main bone cells by different groups [ 55 ]. Recently, LIF was shown to be released into the blood at high levels of mechanical stimulation; conversely, its bone and serum levels decrease in tail-suspended mice, as well as in MLO-Y4 cells grown under random positioning machine (RPM) [ 55 ].…”
Section: Recent Updates On the Responses Of Osteocytes To Weightlessness At The Cellular And Molecular Levelmentioning
confidence: 99%
“…LIF expression has been reported for all three main bone cells by different groups [ 55 ]. Recently, LIF was shown to be released into the blood at high levels of mechanical stimulation; conversely, its bone and serum levels decrease in tail-suspended mice, as well as in MLO-Y4 cells grown under random positioning machine (RPM) [ 55 ]. Khosla’s group identified LIF as one of the factors present in both serum and bone whose levels decrease in post-menopausal women.…”
Section: Recent Updates On the Responses Of Osteocytes To Weightlessness At The Cellular And Molecular Levelmentioning
confidence: 99%
See 1 more Smart Citation